COVID-19 Risk Management and Emotional Reactions to COVID-19 Among School Teachers in Denmark: Results From the CLASS Study - Nabe-Nielsen, Kirsten (J Occup Environ Med, 2021)
OBJECTIVES: We explored teachers’ emotional reactions to the COVID-19 pandemic, and the association between COVID-19 risk management and these emotional reactions. METHODS: We used cross-sectional data from 2665 teachers working at public schools. Participants responded to a questionnaire in May 2020. The analyses were adjusted for sex, age, cohabitation, and region. RESULTS: Knowledge about adequate test behavior and feeling secure regarding colleagues’ actions to hinder spread of virus were associated with less frequent emotional reactions. Lack of access to personal protective equipment and exposure to infected pupils, parents or colleagues were associated with more frequent emotional reactions. CONCLUSION: Similar to other groups of frontline employees, teachers experience negative emotional reactions to the COVID-19 pandemic. Gaining knowledge about teachers’ worries and fears during pandemics is an important first step enabling leaders and occupational health professionals to address these.